Miliary Tuberculosis with Tubercular Uveitis Presenting as Fever of Unknown Origin: A Case Report - Parvin, Roksana; Mutanabbi, Mahbub; Shova, Shamima Sharmin; Kibtiar, Maria; Sharmin, Farzana (Bangladesh Journal of Child Health, 2019)
Miliary tuberculosis is a form of disseminated tuberculosis, which is more frequent in immunocompromised patient. Ocular involvement of mycobacterium tuberculosis is also an uncommon presentation of disseminated tuberculosis. Tubercular uveitis is most frequent form of ocular tuberculosis. If treatment is delayed, it may cause loss of vision. In many case of the systemic TB with ocular involvement, there may be no eye symptoms in early stage. On the other hand, many cases of ocular TB may not have any evidence of systemic TB. Here we have described a case of miliary tuberculosis with ocular uveitis who initially presented with fever without any significant physical findings and later developed eye symptoms including diminished vision. Bangladesh J Child Health 2019; VOL 43 (2) :126-130